ANALISA PENGERING IKAN AIR TAWAR DENGAN MENGGUNAKAN SISTEM HYBRID KOLEKTOR SURYA TIPE RAK DENGAN SOLAR CELL - Jainal Arifin; Muhammad Marsudi (INFO-TEKNIK, 2018)
In South Kalimantan precisely in regency of Hulu Sungai Selatan Amuntai, itis one of the dry fish manufacturing of regency in South Kalimantan. The process ofdrying fish is still doing by traditionally where the fish are drying by utilizing theenergy of the sun directy. The main problem that arise in unfavorable of dryingprocess is a decrease in quality such as a large distribution of water content, thedamage that caused by fungus or biochemical change that unwanted. If thedistribution of heat and air is uneven or uniform, the drying rate of the material willalso be uneven.The method of research was conducted by several stage, first prepare the testequipment, namely fish dryer that has been designed in such a way based on theresult of calculation and then put in the test location and the collector is directed tothe sun and for testing sample by using freshwater fish, sepat fish and haruan fishobtained from the result of local resident, as a measure of temperature in the dryingchamber is using a thermometer to know the temperature in the fish dryer.Based on the data of analysis and discussion, can be taken the conclusionabout fish dryer that is the distribution of the drying rate in the each rack havevariation according to the temperature of the each rack. The result of drying the sepatfish for 7 hours by using solar power dryer were able to reduce the weight of sepatfish from 500 g to 200 g and the wet weight of haruan fish from 500 g to 200 g. Thetotal efficiency of solar power dryer is 79.768%